2016
DOI: 10.3390/en9030169
|View full text |Cite
|
Sign up to set email alerts
|

The Behaviour of Fracture Growth in Sedimentary Rocks: A Numerical Study Based on Hydraulic Fracturing Processes

Abstract: Abstract:To capture the hydraulic fractures in heterogeneous and layered rocks, a numerical code that can consider the coupled effects of fluid flow, damage, and stress field in rocks is presented. Based on the characteristics of a typical thin and inter-bedded sedimentary reservoir, China, a series of simulations on the hydraulic fracturing are performed. In the simulations, three points, i.e., (1) confining stresses, representing the effect of in situ stresses, (2) strength of the interfaces, and (3) materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…36,37 Additionally, local heterogeneity of the rock matrix and the stress fluctuations because of the variability of material properties cause branching, twisting, and turning of fractures. [38][39][40] Various studies 41,42 have been conducted on the interaction between heterogeneity and hydraulic fracturing. The effect of heterogeneity on mechanical and acoustic emission characteristics of rock specimen was also studied under uniaxial compression using numerical simulations.…”
Section: Introductionmentioning
confidence: 99%
“…36,37 Additionally, local heterogeneity of the rock matrix and the stress fluctuations because of the variability of material properties cause branching, twisting, and turning of fractures. [38][39][40] Various studies 41,42 have been conducted on the interaction between heterogeneity and hydraulic fracturing. The effect of heterogeneity on mechanical and acoustic emission characteristics of rock specimen was also studied under uniaxial compression using numerical simulations.…”
Section: Introductionmentioning
confidence: 99%
“…So far, some researches have been made on the influence of bedding planes and natural fractures on hydraulic fracture propagation. Regarding the factors affecting hydraulic fracture propagation, Li et al concluded through numerical simulation that the fracture propagation is primarily influenced by original crustal stress, bedding plane quality as well as the lithologic character. Lu et al also drew a conclusion through the same means that horizontal principal stress difference, minimum horizontal principal stress and intersection angle between hydraulic fracture and stratigraphic interface which are the dominant factors that influence fracture propagation and the forms.…”
Section: Introductionmentioning
confidence: 99%
“…At present, to enhance gas drainage efficiency in a low-permeability coal seam, hydraulic fracturing (HF) is used as a standard practice [1][2][3]. It achieves good results draining coal bed methane in most coal mines.…”
Section: Introductionmentioning
confidence: 99%